1999
DOI: 10.1136/ard.58.5.266
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatic disease and the Australian Aborigine

Abstract: Objective-To document the frequency and disease phenotype of various rheumatic diseases in the Australian Aborigine. Methods-A comprehensive review was performed of the archaeological, ethnohistorical, and contemporary literature relating to rheumatic diseases in these indigenous people. Results-No evidence was found to suggest that rheumatoid arthritis (RA), ankylosing spondylitis (AS), or gout occurred in Aborigines before or during the early stages of white settlement of Australia. Part of the explanation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…35 Other studies have suggested a high prevalence of interracial marriage among IA with RA, 36,37 but in contrast, in a recent unselected population survey, no case of RA was reported in IA. 38 Genetics might explain a low prevalence of RA in IA, as IA rarely harbour the rheumatoid major histocompatibility complex class II shared epitope.…”
Section: Rheumatoid Arthritismentioning
confidence: 83%
See 1 more Smart Citation
“…35 Other studies have suggested a high prevalence of interracial marriage among IA with RA, 36,37 but in contrast, in a recent unselected population survey, no case of RA was reported in IA. 38 Genetics might explain a low prevalence of RA in IA, as IA rarely harbour the rheumatoid major histocompatibility complex class II shared epitope.…”
Section: Rheumatoid Arthritismentioning
confidence: 83%
“…46 Personal observations of antineutrophil cytoplasmic antibody-related vasculitis and dermatomyositis have been reported in IA. 37 There are no published data on the prevalence of primary Sjögren Syndrome, autoimmune thyroiditis, coeliac disease, vitiligo or psoriasis in IA.…”
Section: Autoantibodies In Indigenous Australiansmentioning
confidence: 99%
“…In Iraq a prevalence was reported of 0.07% [70] and in Iran of 0.14 [71]. For Australia, there is no evidence to support the occurrence of AS in the indigenous Australian Aborigines with pure ancestry, probably related to the very low frequency of HLA-B27 in this population [72]. Studies from Latin-America and Africa are scarce.…”
Section: Literature Review On Prevalence and Incidence Spamentioning
confidence: 99%
“…Detailed genetic studies on the Ayatal tribe of Taiwanese Aborigines have recently been performed and are described below. Other Aboriginal populations that have been studied include Australian Aborigines, in whom the occurrence of gouty arthritis was originally reported to be rare [26,27], although the prevalence of hyperuricemia was reported to be higher in Aboriginals compared with non-Aboriginals [28]. A recent report by Chan and Segasothy [29], however, suggests that gout may be more common than previously thought in this native population.…”
Section: Epidemiology Of Hyperuricemia and Gout In Genetically Isolatmentioning
confidence: 94%